OECD reviews of public health : Korea / A healthier tomorrow. (Paris : OECD, 2020)
"This review assesses Korea's public health system, highlights areas of strength and weakness, and makes a number of recommendations for improvement. The review examines Korea's public health system architecture, and how well policies are responding to population health challenges, including the growing burden of chronic disease, and resulting pressures on the health system. In particular, the review assesses Korea's policies to prevent harmful alcohol use, and the risks and opportunities around public health genomics in Korea, which is both a growing field in the health sector, and a booming commercial industry. The review also examines Korea's exposure to public health emergencies, and capacity to respond to emergencies as and when they occur"--Publisher information.
Includes bibliographical references.
Keywords: Public health -- Korea (South)